2017
DOI: 10.1007/s12161-017-1078-9
|View full text |Cite
|
Sign up to set email alerts
|

Using Intact Nuts and Near Infrared Spectroscopy to Classify Macadamia Cultivars

Abstract: Macadamia nut industry is increasingly gaining more space in the food market and the success of the industry and the quality are largely due to the selection of cultivars through macadamia nut breeding programs. Thus, the objective of this study was to investigate the feasibility NIRS coupled to chemometric classification methods, to build a rapid and non-invasive analytical procedure to classify different macadamia cultivars based on intact nuts. Intact nuts of five different macadamia cultivars (HAES 246, IA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Later, Garcia-Molina et al [19] used NIR spectroscopy in combination with partial least square (PLS) analysis to successfully distinguish low gliadin wheat grain from non-transgenic wheat lines with 96% of classification accuracy. It has been shown that using spectroscopic and machine learning algorithms makes it possible to distinguish not only GM and non-GM plants, but also plant species [11,20] and even varieties [21]. However, there is no study that discriminates the GM and non-GM plants with their interspecific hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…Later, Garcia-Molina et al [19] used NIR spectroscopy in combination with partial least square (PLS) analysis to successfully distinguish low gliadin wheat grain from non-transgenic wheat lines with 96% of classification accuracy. It has been shown that using spectroscopic and machine learning algorithms makes it possible to distinguish not only GM and non-GM plants, but also plant species [11,20] and even varieties [21]. However, there is no study that discriminates the GM and non-GM plants with their interspecific hybrids.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, it was clear that LDA had better performance. In another case [ 68 ], PCA-LDA and GA-LDA were used to establish the identification model of macadamia cultivars. Experiments showed that, with Savitzky–Golay smoothing preprocessed spectra, the accuracy of GA-LDA was higher than 94.44%.…”
Section: Traditional Pattern Recognition Methodsmentioning
confidence: 99%
“…The selected variables are of the same scale as the original spectral data and are selected according to the lowest risk of misclassification (G). The value of G is calculated from the validation set according to the following equation described by Carvalho et al (2018):…”
Section: Chemometricsmentioning
confidence: 99%